PEMODELAN JUMLAH KASUS PENYAKIT KUSTA DI PROVINSI JAWA TIMUR - PERTIWI, NI MADE SUKMA; SUKARSA, I KOMANG GDE; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 9 No 1 (2020)DO - 10.24843/MTK.2020.v09.i01.p277, 2020)
Spatial Autoregressive Model (SAR) is a combination of linear regression models with spatial lag in response variables that consider spatial effects.  One problem that considers spatial effects is leprosy cases. This study aims to predict the number of leprosy cases models in East Java Province and the factors that influence it. The type of data used in this study is secondary data obtained from the publication of the Health Profile of East Java Province in 2017 and the publication of the Central Statistics Agency (CSA) of East Java Province. The results of this study indicate that the SAR model can describe the number of leprosy cases in East Java Province with AIC value is 109,951 and value is 71,93%. The factors that influence the number of leprosy cases are the percentage of healthy houses and the number of health centers in each district/city in East Java Province.